The country of memory : remaking the past in late socialist Vietnam - Tai, Hue-Tam Ho, 1948- (Asia--local studies/global themes, 2001)
The American experience in the Vietnam War has been the subject of a vast body of scholarly work, yet surprisingly little has been written about how the war is remembered by Vietnamese themselves. The Country of Memory fills this gap in the literature by addressing the subject of history, memory, and commemoration of the Vietnam War in modern day Vietnam.